Radiology methods of the sarcopenia diagnosis - V. L. Masenko; A. N. Kokov; I. I. Grigoreva; K. E. Krivoshapova (Исследования и практика в медицине, 2019)
One of the processes that accompany the aging of the body and the decline in the quality of life of older people is sarcopenia or loss of muscle tissue and the associated restriction of mobility. The identification of this condition in patients at the stage when there is only an initial decrease in muscle mass without a decrease in muscle strength is of great importance for determining the cause of the disease and the timely start of treatment. This review describes the capabilities of the methods of radiation diagnosis in assessing the quantity and quality of muscle tissue and their shortcomings from the standpoint of verification and dynamic observation of sarcopenia. The lack of a unified standard for the instrumental diagnosis of this pathology and the alertness of specialists regarding sarcopenia during routine examination is one of the main reasons for the insufficient detection of muscle loss in the cohort of elderly patients. This review is of interest to a wide range of clinical physicians and radiologists, who are found in their practice with patients of older age groups.